Studi Infeksi Haemonchus spp Pada Kambing Kacang yang Dipotong di Rumah Potong Hewan Banda Aceh - Mufti Kamaruddin (Agricultural Faculty, 2001)
ABSTRACT.The propose of this study is to find out the prevalence and the severety of Haemonchus spp infection and the comparative count of male and female worms in goats. One hundred abomasums from Abattoir in Banda Aceh were examined with mucous membrane flushing with running water of tap in Parasitology Laboratory of Veterinary Medicine Syiah Kuala University. The result of the study to show that prevalence of Haemonchus spp infection in goats is 87 %, and the severety of infection is 175 worm/goats. The comparative count of male and female worms in goats worm is 1 : 1.